2011
DOI: 10.1242/jcs.087320
|View full text |Cite
|
Sign up to set email alerts
|

The myosin-binding UCS domain but not the Hsp90-binding TPR domain of the UNC-45 chaperone is essential for function in Caenorhabditis elegans

Abstract: SummaryThe UNC-45 family of molecular chaperones is expressed in metazoan organisms from Caenorhabditis elegans to humans. The UNC-45 protein is essential in C. elegans for early body-wall muscle cell development and A-band assembly. We show that the myosin-binding UCS domain of UNC-45 alone is sufficient to rescue lethal unc-45 null mutants arrested in embryonic muscle development and temperature-sensitive loss-of-function unc-45 mutants defective in worm A-band assembly. Removal of the Hsp90-binding TPR doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 57 publications
(95 reference statements)
3
48
1
Order By: Relevance
“…9,31 The myosin levels were similar, in agreement with results in ovarian carcinoma cells, 21 and were distinct from the effects of transgenic UNC-45 overexpression leading to decreased myosin accumulation in C. elegans muscle cells. 13,38 In addition to regulation of UNC-45A gene transcription with distinct patterns of expression from the UNC-45B gene, 20 alternative splicing produced two major mRNAs that are expressed as two protein isoforms. These isoforms differed only § http://www.rcsb.org/pdb/explore/explore.do?…”
Section: Discussionmentioning
confidence: 99%
“…9,31 The myosin levels were similar, in agreement with results in ovarian carcinoma cells, 21 and were distinct from the effects of transgenic UNC-45 overexpression leading to decreased myosin accumulation in C. elegans muscle cells. 13,38 In addition to regulation of UNC-45A gene transcription with distinct patterns of expression from the UNC-45B gene, 20 alternative splicing produced two major mRNAs that are expressed as two protein isoforms. These isoforms differed only § http://www.rcsb.org/pdb/explore/explore.do?…”
Section: Discussionmentioning
confidence: 99%
“…These authors suggest that excess UNC-45 associates with myosin, making it more likely to remain in an unassembled state that is more susceptible to degradation. Ni et al (2011) used extra-chromosomal arrays expressing UNC-45 fragments to show that reductions in myosin levels, A-band assembly and motility are largely dependent on the presence of the UCS domain. Furthermore, the UCS domain is required to partially rescue lethality of an unc-45 null mutant and the motility and A-band assembly of a temperature-sensitive mutant (Ni et al, 2011).…”
Section: Model Organism-based Studies Of Unc-45 Functionmentioning
confidence: 99%
“…Ni et al (2011) used extra-chromosomal arrays expressing UNC-45 fragments to show that reductions in myosin levels, A-band assembly and motility are largely dependent on the presence of the UCS domain. Furthermore, the UCS domain is required to partially rescue lethality of an unc-45 null mutant and the motility and A-band assembly of a temperature-sensitive mutant (Ni et al, 2011). Interestingly, the UCS domain alone appears more effective than full-length UNC-45 on a per molecule basis (Ni et al, 2011).…”
Section: Model Organism-based Studies Of Unc-45 Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of how UNC-45 and DAF-21 work together are still unclear, although it has been reported that UNC-45 interacts with Hsp90 via a TPR domain (Russell et al 1999;Scheufler et al 2000;Barral et al 2002) and myosin motor domains through its COOH-terminal regions (Barral et al 1998(Barral et al , 2002. Elegant studies by Ni et al demonstrated that DAF-21 and UNC-45 interact in pull-down experiments using C. elegans lysates and proposed that this interaction might have an inhibitory effect on the myosin-chaperoning activity of UNC-45 (Ni et al 2011).…”
Section: H S P 9 0 C O -C H a P E R O N E S I N N E M At O D E Smentioning
confidence: 99%